Teacher Performance Evaluation at SDN Wawopada Using the Charlotte Danielson Model - Lagale, Theresia Sertika (Journal of English Language and Education, 2025)
Teacher performance evaluation is essential for improving education quality. This study evaluates teacher performance at SDN Wawopada using the Charlotte Danielson model, which consists of four domains: Planning and Preparation, Classroom Management, Learning Implementation, and Professional Responsibility. The objective is to analyze teacher performance based on these domains and identify areas for improvement. A mixed-method approach combining quantitative and qualitative methods was employed. Data were collected through document studies, observations, questionnaires, and interviews involving 31 respondents, comprising 9 teachers and 22 students. The collected data were analyzed using statistical and descriptive techniques with SPSS version 27 to determine the percentage of scores and categorize teacher performance. The findings indicate that overall teacher performance falls into the "very good" category. Teachers demonstrate strong capabilities in planning, classroom management, instructional delivery, and professional responsibility. However, a key issue identified is the minimal use of teaching media and technology. Despite advancements in digital education tools, many teachers rely on traditional methods, limiting student engagement and learning outcomes. To enhance teacher performance, it is recommended that teachers receive professional development programs focused on technology integration. Increasing access to teaching media, digital platforms, and innovative pedagogical approaches will further improve instructional quality. This study underscores the importance of continuous teacher evaluation to maintain high educational standards and adapt to evolving teaching methodologies.